Traslado de pacientes críticos - Martínez S., Felipe; Avendaño A., Galo; Brinkmann B., Manuela; Cortés M., César (Revista Hospital Clínico Universidad de Chile, 2014)
Critical care transport is a raising need in health care because patients who have medical conditions that exceed the capabilities of the initial treating facility require timely safe transport to referral centers. Therefore, indications for inter-hospital transfer include the need for specialist intervention, a critical bed not available or ongoing support not provided in the referring hospital. The aim of transferring a critically ill patient to a reference center is to improve prognosis, and this potential benefit must outweigh potential harm derived of eventual complications or adverse events that could happen during transportation, because critically ill patients have a high risk of morbidity and mortality during transport. The most frequent indications of transfer involve time-dependent pathologies, such as Cardiovascular and Neurologic Emergencies. Pre-transport evaluation and stabilization is critical, as it contributes to minimize in-transport risks, and it must consider aspects as adequate monitoring, transportation times and conditions.